Designing a Pattern of Extra-Organizational Professional Ethics for Deputies and Heads of Education Districts of Tehran City - Momayez, Shiva; Safari, Mahmoud; Imani, Mohammad Naghi (Iranian Journal of Educational Sociology, 2022)
Purpose: Considering the role and importance of professional ethics in all organizations, including educational organizations, the purpose of this study was designing a pattern of extra-organizational professional ethics of deputies and heads of education districts. Methodology: The present study in terms of purpose was applied and in terms of implementation method was combined (qualitative and quantitative). The research population in both qualitative and quantitative sections were deputies and heads of education districts of Tehran city in 2018-19 academic years, which The sample size in the qualitative section according to the principle of theoretical saturation was estimated 20 people who were selected by purposive sampling method and the sample size in the quantitative section according to Cochran's formula was estimated 113 people who were selected by cluster random sampling method. The research instruments were semi-structured interview and researcher-made questionnaire whose psychometric properties were confirmed. Data were analyzed by methods of coding and exploratory factor analysis. Findings: The results of the qualitative section showed that extra-organizational professional ethics included 71 indicators in 14 categories of professional, ethical or normative, ethical knowledge, organizational strategies, education, managerial factors, resources, institutionalization, evaluation, staff, organizational culture, structure factors, organizational procedures or regulations and development of individual and organizational professional ethics. Also, the results of the quantitative section showed that extra-organizational professional ethics included 40 items in 9 factors of self-efficacy, scientific responsibility, individual ethics, managerial factors, organizational factors, job ethics, extra-organizational factors, social responsibility and belonging to scientific social, which two factors of self-efficacy and belonging to scientific social were removed from the pattern due to a factor load of less than 0.40. Finally, the pattern of extra-organizational professional ethics of deputies and heads of education districts was designed. Conclusion: According to the designed pattern of extra-organizational professional ethics of the deputies and heads of education districts, to promote the extra-organizational professional ethics in them can be improved the identified categories.